2022
DOI: 10.3390/v14050859
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mechanism of a Highly Virulent Infectious Hematopoietic Necrosis Virus in Head Kidney of Rainbow Trout (Oncorhynchus mykiss) Analyzed by RNA-Seq Transcriptome Profiling

Abstract: Infectious hematopoietic necrosis virus (IHNV) is a pathogen that causes high rates of mortality in salmonid fishes. Therefore, an RNA-seq-based transcriptome analysis was performed in the head kidney of rainbow trout infected with a highly virulent IHNV strain to understand the pathogenesis of and defense strategies for IHNV infection in rainbow trout. The results showed that the numbers of DEGs were 618, 2626, and 774 (control vs. IHNV) on days 1, 3, and 5, respectively. Furthermore, the enrichment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Furthermore, TRIM63 is also probably involved in other processes (e.g., targeting pro-anabolic factors, intracellular trafficking) and, as other members of its family, seems to have emerging roles in innate immunity, since it is induced by IFNs [ 45 , 46 ]. Interestingly, Kim et al found TRIM25 , a protein belonging to the same family as the above mentioned one, among up-regulated DEGs in rainbow trout infected with a highly virulent strain of infectious hematopoietic necrosis virus (IHNV; family Rhabdoviridae ) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TRIM63 is also probably involved in other processes (e.g., targeting pro-anabolic factors, intracellular trafficking) and, as other members of its family, seems to have emerging roles in innate immunity, since it is induced by IFNs [ 45 , 46 ]. Interestingly, Kim et al found TRIM25 , a protein belonging to the same family as the above mentioned one, among up-regulated DEGs in rainbow trout infected with a highly virulent strain of infectious hematopoietic necrosis virus (IHNV; family Rhabdoviridae ) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, some GO terms related to the immune system appeared identical in both strains in terms of timing and score, e.g., “tumour necrosis factor-mediated signalling pathway” and “regulation of interferon-gamma-mediated signalling pathway”. Regarding the latter GO, Kim et al [ 47 ] reported its enrichment at 3 dpi during a similar experimental trial performed using the other salmonid Novirhadbovirus (IHNV). Tumour necrosis factor (TNF) is a type II transmembrane protein expressed in the plasma [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The screening criteria for differentially expressed genes (DEGs) were |logFC| > 1 and FDR <0.05. Finally, mRNAs differentially expressed in IDD were obtained 27 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, mRNAs differentially expressed in IDD were obtained. 27 Screening for Core Genes of IDD in the Mouse Model Differentially expressed mRNAs from mice with IDD were obtained based on the transcriptome sequencing difference analysis. the GeneCard database was used, and with "Intervertebral disc degeneration" as the search condition, the top 1000 genes were selected as the genes related to IDD by "Relevance score."…”
Section: Ivd Tissue Collection For Transcriptome Sequencingmentioning
confidence: 99%
“…Intensive farming conditions have contributed to economic growth while also leading to complex aquatic environments that make rainbow trout susceptible to pathogens ( 3 ). Infectious hematopoietic necrosis virus (IHNV), which belongs to the genus Novirhabdovirus of the family Rhabdoviridae, is highly pathogenic and widely transmissible, causing not only high mortality in rainbow trout but also brings huge economic losses to the global aquaculture industry ( 4 , 5 ). Vaccines have long been the main choice for preventing viral diseases, but their efficacy is limited by financial constraints.…”
Section: Introductionmentioning
confidence: 99%